2021
DOI: 10.1002/alz.12413
|View full text |Cite
|
Sign up to set email alerts
|

Protective association of the ε2/ε3 heterozygote with Alzheimer's disease is strengthened by TOMM40–APOE variants in men

Abstract: Introduction Despite advances, understanding the protective role of the apolipoprotein E (APOE) ε2 allele in Alzheimer's disease (AD) remains elusive. Methods We examined associations of variants comprised of the TOMM40 rs8106922 and APOE rs405509, rs440446, and ε2‐encoding rs7412 polymorphisms with AD in a sample of 2862 AD‐affected and 169,516 AD‐unaffected non‐carriers of the ε4 allele. Results Association of the ε2/ε3 heterozygote of men with AD is 38% (P = 1.65 × 10−2) more beneficial when it is accompani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…None of these group-specific SNP-metabolite associations were significant in the pooled sample of the E2, E3, and E4 groups. The group-specific associations indicate genetic heterogeneity of plasma metabolites in the APOE 19q13.3 locus, which is in line with our previous studies that demonstrated complex LD structure differentially affects AD risk in this locus (Kulminski et al, 2018(Kulminski et al, , 2020aNazarian et al, 2022a,b). Therefore, we suggest APOE-stratified analyses are essential for dissecting the genetic architecture of complex diseases and traits sensitive to APOE ε2/ε3/ε4 polymorphism.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…None of these group-specific SNP-metabolite associations were significant in the pooled sample of the E2, E3, and E4 groups. The group-specific associations indicate genetic heterogeneity of plasma metabolites in the APOE 19q13.3 locus, which is in line with our previous studies that demonstrated complex LD structure differentially affects AD risk in this locus (Kulminski et al, 2018(Kulminski et al, , 2020aNazarian et al, 2022a,b). Therefore, we suggest APOE-stratified analyses are essential for dissecting the genetic architecture of complex diseases and traits sensitive to APOE ε2/ε3/ε4 polymorphism.…”
Section: Discussionsupporting
confidence: 90%
“…The APOE 19q13.3 locus is a genetically heterogenous region within which complex haplotype structures, interactions, and compound genotypes have been identified (Templeton et al, 2005;Yu et al, 2007;Lescai et al, 2011;Lutz et al, 2016;Babenko et al, 2018;Kulminski et al, 2018Kulminski et al, , 2020aKulminski et al, ,b, 2021Zhou et al, 2019;Nazarian et al, 2022a,b). For instance, linkage disequilibrium (LD) and association studies have highlighted complex genetic structure in this locus that are statistically different between AD-affected and unaffected subjects (Kulminski et al, 2018(Kulminski et al, , 2020a. In addition, stratified 10.3389/fnagi.2022.1023493 analyses have identified sets of interactions and compound genotypes in the APOE locus of the ε2and ε4-carriers, which may modify the effects of these alleles on AD risk and, to some extent, justify their incomplete penetrance (Nazarian et al, 2022a,b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite strong associations between APOE and AD, neither the ε2 nor ε4 allele is considered as a causal factor for AD development [5,[8][9][10]. Addressing the mechanisms of actions of the ε2 and ε4 alleles is essential for understanding AD pathogenesis and AD risk assessment.…”
Section: Introductionmentioning
confidence: 99%
“…The second is at best the indirect role of evolution in mechanisms of age‐related traits (Nesse et al, 2012 ). Accordingly, the genetic contributions to age‐related traits could manifest in various forms including, for example, the impacts of causal variants, structural diversity of the genome, intricate genetic architectures of complex traits, combinations of risk alleles, haplotypes, and combinations of genotypes (called compound genotypes) (Eichler et al, 2010 ; Franceschi et al, 2018 ; Gibson, 2012 ; Kulminski et al, 2021 ; Rogaev et al, 1995 ; Wainberg et al, 2020 ; Zhou et al, 2019 ). Dissecting the genetic complexity is a challenging task as exemplified by the well‐studied apolipoprotein E ( APOE ) ε2/ε3/ε4 polymorphism; despite decades of APOE research, its role in age‐related traits is still unclear (Belloy et al, 2019 ; Genin et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%